2020
DOI: 10.1021/acs.jpcc.9b10935
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-Bond-Controlled Self-Assembly of Regioisomeric Phenanthridine Derivatives into Nanowires and Nanosheets

Abstract: The spectroscopic and photophysical properties of organic materials in the films are widely influenced by their molecular packing morphologies and intermolecular interactions. Here, regioisomeric phenanthridine derivatives were synthesized. The UV–vis spectra and scanning electron microscopy images show that these molecules can form different self-organizations in the films. Scanning tunneling microscopy and density functional theory calculations are utilized to reveal their intermolecular interactions by visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 42 publications
(65 reference statements)
0
21
1
Order By: Relevance
“…Experimentally, halogen-bond mediated intermolecular interactions have been reported to influence the spectroscopic and photophysical properties of organic film materials. 118 In regioisometric phenanthridine derivatives, it was shown that the different intermolecular Br•••N halogen bonds, H•••Br hydrogen bonds, and Br•••Br type-II halogen bonds were the dominant factors in determining the different nanostructures and film morphologies. SEM images provided further insights of the self-assembly process, as shown in Figure 15.…”
Section: Controllable Functionalized Surfacesmentioning
confidence: 99%
“…Experimentally, halogen-bond mediated intermolecular interactions have been reported to influence the spectroscopic and photophysical properties of organic film materials. 118 In regioisometric phenanthridine derivatives, it was shown that the different intermolecular Br•••N halogen bonds, H•••Br hydrogen bonds, and Br•••Br type-II halogen bonds were the dominant factors in determining the different nanostructures and film morphologies. SEM images provided further insights of the self-assembly process, as shown in Figure 15.…”
Section: Controllable Functionalized Surfacesmentioning
confidence: 99%
“…2.8. Self-Assembled Patterns of Phenanthridine Derivatives at the Liquid/HOPG Interface Four regioisomeric phenanthridine derivatives with different positions of halogen substituents and alkoxy chains (2,9-BHP, 2,9-BHPO, 3,8-BHP, and 3,8-BHPO) (Scheme 1j and Figure 13a-d) were synthesized in order to investigate the XBs in 2D self-assembled nanostructures by STM at the 1-phenyloctane/HOPG interfaces [85]. For 2,9-BHP and 3,8-BHP molecules, these two molecules form linear structures with the π-conjugated cores parallel to each other in each lamella (Figure 13i,k).…”
Section: Self-assembled Patterns Of Phenanthrene Derivatives At the Liquid/hopg Interfacementioning
confidence: 99%
“…The stronger intermolecular XBs and HBs are the dominated forces to govern the arrangement of 2,9-BHP and 3,8-BHP molecules in 2D self-assembled adlayers. [85] with permission from the American Chemical Society.…”
Section: Self-assembled Patterns Of Phenanthrene Derivatives At the Liquid/hopg Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…The phenanthridine derivatives with different positions of bromine and side chain substituents formed entirely different self-assembly patterns, resulting in the directionality of halogen bonds. 45 The solvent effect on halogen-bonded self-assembly nanostructures of 2,9-dibromo-6-(hexadecyloxy)phenanthridine was also explored. Although solvents take part in the self-assembly process, the intermolecular interaction and molecular arrangement remain the same at different solution concentrations, resulting in the strong intermolecular N•••Br•••H halogen bonds and H•••Br hydrogen bonds, so the vdW interactions are not competitive with them.…”
Section: ■ Introductionmentioning
confidence: 99%